2018
DOI: 10.1017/s002210901700120x
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Risk-Taking Incentive and Firm Innovation: Evidence from FAS 123R

Abstract: We investigate how chief executive officers’ (CEOs) risk incentive (VEGA) affects firm innovation. To establish causality, we exploit compensation changes instigated by the FAS 123R accounting regulation in 2005 that mandated stock option expensing at fair values. Our identification tests indicate a positive and causal effect of CEOs’ VEGA on innovation activities. Furthermore, dampened managerial risk-taking incentive after the implementation of FAS 123R leads to a significant reduction in innovation related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(93 citation statements)
references
References 56 publications
9
81
0
3
Order By: Relevance
“…Such studies have observed incentive schemes to not only impact firm productivity, firm value and profitability (Jensen and Murphy, 1990;Sun et al, 2009;Nguyen, 2018) but also corporate social performance (Deckop et al, 2006). The results also complement more recent studies that observe CEO risk-taking incentives to encourage risky investments (Chen, 2017), as well as enhance innovation output quantity and quality (Mao and Zhang, 2018),…”
Section: Ceo Dominance and Firm Innovationsupporting
confidence: 79%
“…Such studies have observed incentive schemes to not only impact firm productivity, firm value and profitability (Jensen and Murphy, 1990;Sun et al, 2009;Nguyen, 2018) but also corporate social performance (Deckop et al, 2006). The results also complement more recent studies that observe CEO risk-taking incentives to encourage risky investments (Chen, 2017), as well as enhance innovation output quantity and quality (Mao and Zhang, 2018),…”
Section: Ceo Dominance and Firm Innovationsupporting
confidence: 79%
“…Moreover, managers having shares within the organization compel him to intensify the organizational innovation. Keeping this view in the same vein, Mao [19] revealed that compensation packages also allure CEOs to orientate towards innovation. Galasso [16] that overconfident CEOs are over-optimistic and always take the risky decisions which ultimately orientate them to invest more in innovation.…”
Section: Corporate Governance and Innovationmentioning
confidence: 97%
“…Manifestly, a voluminous literature has already evaluated the attributes of CEO influencing the innovation within the organization. In this regard, the prior literature has contemplated that, overconfidence, personal links, young age and alluring compensation packages of the incumbent CEO orientate him or her towards innovative adaptability [16][17][18][19]. However, it is not being able to evaluate the aftermath of CEO succession on innovation.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to innovation output, researchers primarily consider the number of patents (e.g., Balsmeier, Buchwald, & Stiebale, 2014;Mao & Zhang, 2018) and patent citations (e.g., Faleye, Hoitash, & Hoitash, 2011;Martin, Washburn, Makri, & Gomez-Mejia, 2015).…”
Section: Innovation Outputmentioning
confidence: 99%
“…Whereas earlier studies often used simple approaches, such as lagging variables or conducting additional subgroup analyses as indicators for causal relationships (e.g., Barker & Mueller, 2002;Deutsch, 2007), recent studies employ more sophisticated methods, such as incorporating fixed effects (e.g., Ammann, Horsch, & Oesch, 2016;Makri, Lane, & Gomez-Mejia, 2006), employing two-stage analyses (e.g., Gerstner, König, Enders, & Hambrick, 2013;Maula, Keil, & Zahra, 2013), or using suitable instrument variables (e.g., Chemmanur, Kong, Krishnan, & Yu, 2019;Kini & Williams, 2012). In addition, some scholars use matched sample approaches (e.g., Ammann, Horsch, & Oesch, 2016;Cremers, Litov, & Sepe, 2017) or examine changes in innovation outcomes after exogenous events, such as exogenous executive turnover (e.g., Balsam, Puthenpurackal, & Upadhyay, 2016;Cummings & Knott, 2018) and regulatory changes (e.g., Balsmeier, Fleming, & Manso, 2017;Mao & Zhang, 2018) or shocks, such as terrorist attacks and the Lehman Brothers bankruptcy (Hutton, Jiang, & Kumar, 2014).…”
Section: Endogeneitymentioning
confidence: 99%